2008
DOI: 10.1021/es702897y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multiple Hormonal Activities in Wastewater Effluents and Surface Water, Using a Panel of Steroid Receptor CALUX Bioassays

Abstract: It is generally known that there are compounds present in the aquatic environment that can disturb endocrine processes, for example via interaction with the endogenous hormone receptors. Most research so far has focused on compounds that bind to the estrogen and/or androgen receptor, but ligands for other hormone receptors might also be present. In this study, a newly completed panel of human cell derived CALUX reporter gene bioassays was utilized to test water extracts for estrogen (ER), as well as androgen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
159
1
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(186 citation statements)
references
References 40 publications
23
159
1
3
Order By: Relevance
“…Specific receptor-mediated modes of action including estrogenic and androgenic effects showed the most promise for routine water quality screening applications. Recent work using GR-CALUX applied to various environmental chemicals and water samples 33 also support our findings that GR activity is present and could be detected in secondary treated effluent with the current battery of GR bioassays. In addition, given the co-occurrence of progestins and synthetic estrogens in hormone replacement therapy, PR activity remains of interest, despite the negative findings here.…”
Section: ■ Resultssupporting
confidence: 86%
“…Specific receptor-mediated modes of action including estrogenic and androgenic effects showed the most promise for routine water quality screening applications. Recent work using GR-CALUX applied to various environmental chemicals and water samples 33 also support our findings that GR activity is present and could be detected in secondary treated effluent with the current battery of GR bioassays. In addition, given the co-occurrence of progestins and synthetic estrogens in hormone replacement therapy, PR activity remains of interest, despite the negative findings here.…”
Section: ■ Resultssupporting
confidence: 86%
“…The androgenic potency in Swedish domestic STP effluents varied from not detected to 160 ng DEQ/L [38], which is slightly higher than the potencies in the four STP effluents from the present study. Androgenic activity was less frequently detected in surface water and sediment of the Pearl River system, which is consistent with the results of some previous studies [13,39,40]. The possible explanation for the lower androgenic activity is that the agonistic androgenic potency might be masked by androgen receptor antagonists in the extracts [12,40].…”
Section: Discussionsupporting
confidence: 91%
“…Effluents from pulp and paper mills displayed androgenic activity in female fish, leading to masculinization or sex reversal of female fish [10,11]. Very recently, screening assays revealed that androgenic activity also exists widely in industrial and hospital wastewaters, municipal STP effluents, and even in surface water in association with estrogen, progesterone, and glucocorticoid receptor activities [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of endocrine disruption is even more complex as mixtures of compounds with different endocrine effects might enhance or counteract each other or act independent of each other (Brian et al 2005;Houtman et al 2006b;Weiss et al 2009). Several surveys have demonstrated the presence of (anti-) androgens, glucocorticoids, and thyroid hormone activities in the environment (Houtman et al 2004a; Van der Linden et al 2008;Chang et al 2009;Weiss et al 2009). However, thyroid hormone activity was not detected in a survey investigating drinking water prepared from the French river Seine (Jugan et al 2009).…”
Section: Endocrine Disrupting Compoundsmentioning
confidence: 99%